“Some Real War Shit. … I Fucking Held the Camera”: Re-implacing Iraq in Roy Scranton’s War Porn (2016) - Barbara Kowalczuk (Sillages Critiques)
Drawing upon Edward S. Casey’s philosophy of place (Remembering: A Phenomenological Study, 1987), this analysis of “strange hells (columbus day, 2004),” one of the three sections composing Roy Scranton’s War Porn (2016), focuses on two forms of the Irreparable, torture and rape. “strange hells” shows how former National Guard soldier Aaron Stojanowski remains the subject of a place, Camp Crawford, an Iraqi detention center where he witnessed and perpetrated acts of torture and abuse. Recalling the human rights violations photographed at Abu Ghraib in 2003, Aaron’s “war porn” triggers re-implacing, that is, remembering and re-experiencing a past place (Casey). The fictional representation of re-implacing the Iraqi prison, now an incorporated foreign body, calls for an ethical response to the suffering of others and the ontological recognition of the grievability of lives (Judith Butler, Frames of War [2009]).